The Popularizing of Sunni Doctrine in Southeast Asia: Sifat Dua Puluh in Malay Kitab Jawi in the 19th Century - Burhanudin, Jajat (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
Sifat Dua Puluh (twenty attributes of God) is a specific term of Malay to convey the doctrine of the Sunni school in Southeast Asia. Adapted from a renowned book of Yusuf al-Sanusi, Umm al-Barāhīn, this term began to appear in the 19th century as a leading Islamic theme in the kitab Jawi of Malay scholars in Mecca (Jawa). The scholars translated the book into Malay and expounded its contents in the form of commentaries (sharḥ), a rising style of writing kitab Jawi on the doctrine of the period. This article is to present a historical analysis of the way Sifat Dua Puluh became an established concept of Sunni theology in the Southeast Asian context, which served to convey the Sunni creeds in a popularly vernacular expression of the Muslims in the region. Sifat Dua Puluh was taken as the Islamic subject transmitted of the period, alongside the reprinting of kitab Jawi to disseminate the concept to Southeast Asia.